Effectiveness of Mattabe’ Culture Integrated Pancasila Education Teaching Modules in Improving Learning Outcomes - Sudarmin, Sudarmin; Munirah, Munirah; Sukmawati, Sukmawati (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2024)
This research aims to analyze the effectiveness of the Mattabe’ cultural integrated Pancasila education teaching module in improving student learning outcomes in elementary schools. The research method used was quantitative using an experimental class with a random control group design. The research sample consisted of randomly selected schools in certain areas, with one group receiving learning using Pancasila education teaching modules integrated with Mattabe’ culture to improve learning outcomes and the other group as a control who continued to use teaching modules that were not integrated with Mattabe’ culture. Data was collected through posttest learning outcomes which were analyzed using the Kruskal-Wallis Test to test significant differences between the two groups. The research results showed that students who studied using the Pancasila education module experienced a significant increase in understanding and academic achievement compared to the control group. These findings support the importance of integrating Mattabe’ culture in education as a strategy to increase the relevance and effectiveness of learning. Sustainable implementation of the Mattabe culture integrated Pancasila education teaching module in improving learning outcomes in elementary schools.